Competitive analysis for stochastic influenza model with constant vaccination strategy. Issue 6 (4th October 2019) - Baleanu, Dumitru; Raza, Ali; Rafiq, Muhammad; Arif, Muhammad Shoaib; Ali, Muhammad Asghar
Abstract : This manuscript discusses a competitive analysis of stochastic influenza model with constant vaccination strategy. The stochastic influenza model is comparatively more pragmatic versus the deterministic influenza model. The effect of influenza generation number holds in the stochastic model. If the value of this number is less than one, this situation will help us to control the disease in a population. A greater than one value of this threshold number shows the persistence of disease to become endemic. The proposed structure for the stochastic influenza model as stochastic non‐standard finite difference scheme conserve all vital characteristics like positivity, boundedness and dynamical consistency defined by Mickens.